DESIGN OF SEMI AUTOMATIC ICE CREAM MAKER AS AN EDUCATIONAL LABORATORY TOOL - Siswara, Hamzah Nata; Veilani, Tomi Mahendra (Jurnal Sains dan Teknologi Industri Peternakan, 2023)
Making ice cream on a laboratory scale generally still uses conventional methods. The process of making ice cream in the conventional way or by manual stirring by human hands is considered inefficient because it takes a long time to make. Thus, it is necessary to evaluate the manufacture of a semi-automatic ice cream maker with considerations of efficiency, effectiveness, and ergonomics. In making this semi-automatic ice cream maker, it has several components, namely making the main frame, making dough tubes and ice cube tubes as temperature controllers, and stirrers. Making ice cream using 4 treatments of stirring time, namely P1 15 minutes, P2 30 minutes, P3 45 minutes, P4 60 minutes. The ingredients used are 67% pure milk, 10% skim milk, 10% sugar, 12% whipping cream, 0.5% CMC, and 0.5% gelatin. The testing phase uses ice cream overrun measurements. The longer the stirring, the higher the overrun value. Based on the results it can be concluded that the semi-automatic ice cream maker was successfully made at an affordable price. Based on the overrun value test, the best results were found in P4 with a stirring time of 60 minutes. Semi-automatic ice cream maker can be used to support milk processing in the laboratory. Keywords: Ice cream maker, ice cream overrun.